1) [2(x + y) - x + 6 = 0,3x - (x - y) = 0; 3) (5x – 2(y + 4) = 0,6(2x + 3) - y - 41 = 0; 2) [3(x + 2y) - y - 27 = 0,14(x + y) - 3x – 23 = 0; 4) (2x + 3(x + y) - 11 = 0,17 (x + 3y) - 6x +59 = 0. ​ это системы уравнений

александрадейкун александрадейкун    2   14.05.2019 20:54    0

Ответы
rytryt rytryt  12.05.2020 19:21

1)2(х+у)-х+6=0

2х+2у-х+6=0

х+2у+6=0

х=-2у-6

3х-(х-у)=0

3х-х+у=0

2х+у=0

2х=-у

2)3(х+2у)-у-27=0

3х+6у-у-27=0

3х+5у-27=0

3х=-5у+27

+9

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика